2014
DOI: 10.1111/nph.12880
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of YODA and mitogen activated protein kinase 6 in Arabidopsis post‐embryogenic root development through auxin up‐regulation and cell division plane orientation

Abstract: Summary The role of YODA MITOGEN ACTIVATED PROTEIN KINASE KINASE KINASE 4 (MAPKKK4) upstream of MITOGEN ACTIVATED PROTEIN KINASE 6 (MPK6) was studied during post-embryonic root development of Arabidopsis thaliana. Loss- and gain-of-function mutants of YODA (yda1 and ΔNyda1) were characterized in terms of root patterning, endogenous auxin content and global proteomes.We surveyed morphological and cellular phenotypes of yda1 and ΔNyda1 mutants suggesting possible involvement of auxin. Endogenous indole-3-acetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 76 publications
5
94
0
1
Order By: Relevance
“…One notable example is the identification of a microtubule minus-end directed calmodulin-binding kinesin in A. thaliana (Reddy et al, 1996a,b) which is conserved in monocots and dicots but does not seem to have orthologues in mammals, yeast, fruit fly, Caenorhabditis elegans or red algae (Abdel-Ghany et al, 2005). Two other unique plant kinesins were identified in rice, one of which simultaneously binds to microtubules and actin microfilaments via calponin homology domain (O. sativa Kinesin with Calponin Homology1; OsKCH1; Frey et al, 2009Frey et al, , 2010 having orthologues in tobacco (NtKCH; Klotz and Nick, 2012) and cotton (GhKCH1 and GhKCH2; Preuss et al, 2004;Xu et al, 2009) (Smékalová et al, 2014). A. Cortical microtubules of post-mitotic root epidermal cells, exhibiting various organization patterns.…”
Section: Microtubule Associated Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…One notable example is the identification of a microtubule minus-end directed calmodulin-binding kinesin in A. thaliana (Reddy et al, 1996a,b) which is conserved in monocots and dicots but does not seem to have orthologues in mammals, yeast, fruit fly, Caenorhabditis elegans or red algae (Abdel-Ghany et al, 2005). Two other unique plant kinesins were identified in rice, one of which simultaneously binds to microtubules and actin microfilaments via calponin homology domain (O. sativa Kinesin with Calponin Homology1; OsKCH1; Frey et al, 2009Frey et al, , 2010 having orthologues in tobacco (NtKCH; Klotz and Nick, 2012) and cotton (GhKCH1 and GhKCH2; Preuss et al, 2004;Xu et al, 2009) (Smékalová et al, 2014). A. Cortical microtubules of post-mitotic root epidermal cells, exhibiting various organization patterns.…”
Section: Microtubule Associated Proteinsmentioning
confidence: 99%
“…A cell similar to that depicted in (a) but with cortical microtubules arranged parallel to each other and transversely oriented with respect to the cell axis. Such cells exhibit longitudinal growth as exemplified by elongating root epidermal cells of A. thaliana (Smékalová et al, 2014). C. A cell entering growth phase with randomly arranged cortical microtubules will undergo isotropic growth resulting in cell bulging.…”
Section: Plant Actin-binding Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Ove cka et al (2015) showed live coimaging of actin filaments and microtubules in the cotyledon epidermal cells, while von Wangenheim et al (2016) tracked cell fate by simultaneous imaging of plasma membrane and nuclear markers during lateral root formation. LSFM, unlike other live cell-imaging techniques, was able to successfully localize signaling protein such as mitogenactivated protein kinase 6 (MPK6) to the preprophase band of Arabidopsis root meristematic cells (Smékalová et al, 2014). One possible target of MPK6 is plantspecific EB1c.…”
Section: Lsfmmentioning
confidence: 99%
“…The main reason for this may be the multifunctional nature of MPK6, which plays essential roles in plant stress responses, growth, and development (Nakagami et al, 2005;Xing et al, 2008Xing et al, , 2009Schikora et al, 2011;Dutilleul et al, 2012;Xu and Zhang, 2015). Actually, MPK6 is a common target among several MAPK cascades Meng et al, 2012;Smékalová et al, 2014). Another possibility is the mutants of AIK1 and MKK5 used for phenotype analysis are the knockdown mutants (the aik1 knockout mutant probably is lethal).…”
Section: Mkk5-mpk6 Are the Downstream Targets Of Aik1 In Aba Signalingmentioning
confidence: 99%